5(x+3)+x=-15

Simple and best practice solution for 5(x+3)+x=-15 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(x+3)+x=-15 equation:


Simplifying
5(x + 3) + x = -15

Reorder the terms:
5(3 + x) + x = -15
(3 * 5 + x * 5) + x = -15
(15 + 5x) + x = -15

Combine like terms: 5x + x = 6x
15 + 6x = -15

Solving
15 + 6x = -15

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-15' to each side of the equation.
15 + -15 + 6x = -15 + -15

Combine like terms: 15 + -15 = 0
0 + 6x = -15 + -15
6x = -15 + -15

Combine like terms: -15 + -15 = -30
6x = -30

Divide each side by '6'.
x = -5

Simplifying
x = -5

See similar equations:

| 17-7x=-25 | | 6(4x-1)=3 | | 17+5x=37 | | 4x^2=-4x+12 | | 6x^2=8000000 | | 6x+8=3-(7x-7) | | 6(x-4)-3=27 | | kx^2-5x+1=0 | | 1p-5=3p+2 | | 4x=10-(x+20) | | 10x^2+6=206 | | 8(x+6)=96 | | 14x^2-34x+14=0 | | 4n^2+7n+10=0 | | 5a=21+2q | | -(7x-(2x+3))=-6(3(3x-4)-2x) | | x^2+x=10x | | f(x)=-x^2+16x | | -(6z-(11z+3))=3+(4z+6) | | 4x=9x-12 | | -2(3m+6)-(4m-3)=21 | | 24x+25=49 | | 5a^2-44=81 | | -20/38/4 | | -4x=y+2 | | 3x+9=8-(2x-2) | | Sinx=0.99x | | 396+x=407 | | x-30=12 | | (2x-4)-(6x-3)=7 | | x(x+1)=5(x+(x+1))-5 | | 3z/8-5=3 |

Equations solver categories